How we have treated and cared patients with Duchenne muscular dystrophy and severe congestive heart failure - Saito, Toshio; Shinno, Susumu (No to hattatsu, 2005)
Patients with Duchenne muscular dystrophy (DMD) and severe congestive heart failure (CHF) frequently feel mental anguish due to severe mental and physical restriction. Since therapy is not efficacious enough, their quality of life is often disturbed during the terminal stage. We retrospectively evaluated the treatment and care for 11 cases of DMD with severe CHF in our hospital. All cases had unrest and anxiety, which were successfully treated with benzodiazepines and haloperidol. In many cases, patients' families craved for patients' comfort without mental and physical pain. Nine cases resulted in death and 2 cases survived. We also sent a questionnaire to doctors of muscular dystrophy wards of 27 Japanese national hospital, inquiring about therapy protocol, monitoring system, intravenous nutrition, limitation of feeding/recreation/visitors, management of pain/anxiety/sedation, and cardiopulmonary resuscitation (CPR). Sixty-eight doctors answered the questionnaire. Forty-seven doctors (69%) had the experience to treat DMD patients with severe CHF. The majority of them monitored electrocardiography, SpO2 and blood pressure. About a half adopted intravenous nutrition. If recovery was expected, limitation of feeding/recreation/visitors was based mainly on discussion with the patients and their families. If recovery was impossible, the limitation was decided according to their wishes. Nonsteroidal anti-inflammatory drugs were properly used for pain, and minor and major tranquilizers for sedation. Morphine was also used. Only one doctor adopted positive CPR, while the others answered "do not CPR" or "do CPR according to the wish of patients' families". The burden to patients and their families during treatment is unavoidable but should be reduced as much as possible. Medical staffs should ask themselves about the problems to support the families as well as patients repetitively.